REKONSTRUKSI TEORETIS BAHAN AJAR PAI: INTEGRASI LITERASI MEDIA DALAM PENGEMBANGAN MODUL DIGITAL DI ERA DISRUPSI - M. Soinun Amrillah; Helmi Handoko; Abdurrahmansyah; Nurlaila (STKIP Subang, 2026)
The massive development of digital technology demands a transformation of the Islamic Religious Education (PAI) learning paradigm from conventional methods to interactive and adaptive learning resources. However, the abundance of digital information flows raises challenges in the form of the risk of exposure to extreme beliefs that require critical filtering abilities through media literacy in teaching materials. This research aims to theoretically analyze the transformation of PAI teaching materials through the development of modules that integrate aspects of media literacy. This research uses a library research method with procedures for determining topics, searching for information, evaluating sources, and analyzing data. Literature was collected through the Google Scholar database and digital libraries with the inclusion criteria of national and international journal articles published between 2019–2025 which focus on PAI digital modules and media literacy. Data were analyzed using content analysis techniques to synthesize the module development model. The study shows that the transformation of PAI teaching materials requires the application of systematic instructional design, such as the ADDIE model, which integrates the values ​​of religious moderation and digital ethics as information filtering instruments. Media literacy in the PAI module has proven to be crucial for building students' learning independence and critical thinking. The development of PAI modules based on media literacy is a strategic step to create learning that is relevant and able to answer the challenges of information disruption, with important implications for strengthening the digital competence of PAI teachers